Small-molecule-mediated chemical knock-down of MuRF1/MuRF2 and attenuation of diaphragm dysfunction in chronic heart failure - Adams, Volker; Lewis, Joe; Provaznik, Jan; Benes, Vladimir; Gasch, Alexander; Witt, Christian; Labeit, Dittmar; Labeit, Siegfried (Journal of cachexia, sarcopenia and muscle, 2019)
Background Chronic heart failure (CHF) leads to diaphragm myopathy that significantly impairs quality of life and worsens prognosis. In this study, we aimed to assess the efficacy of a recently discovered small-molecule inhibitor of MuRF1 in treating CHF-induced diaphragm myopathy and loss of contractile function. Methods Myocardial infarction was induced in mice by ligation of the left anterior descending coronary artery. Sham-operated animals (sham) served as controls. One week post-left anterior descending coronary artery ligation animals were randomized into two groups—one group was fed control rodent chow, whereas the other group was fed a diet containing 0.1% of the compound ID#704946—a recently described MuRF1-interfering small molecule. Echocardiography confirmed development of CHF after 10 weeks. Functional and molecular analysis of the diaphragm was subsequently performed. Results Chronic heart failure induced diaphragm fibre atrophy and contractile dysfunction by 20%, as well as decreased activity of enzymes involved in mitochondrial energy production (P < 0.05). Treatment with compound ID#704946 in CHF mice had beneficial effects on the diaphragm: contractile function was protected, while mitochondrial enzyme activity and up-regulation of the MuRF1 and MuRF2 was attenuated after infarct. Conclusions Our murine CHF model presented with diaphragm fibre atrophy, impaired contractile function, and reduced mitochondrial enzyme activities. Compound ID#704946 rescued from this partially, possibly by targeting MuRF1/MuRF2. However, at this stage of our study, we refrain to claim specific mechanism(s) and targets of compound ID#704946, because the nature of changes after 12 weeks of feeding is likely to be complex and is not necessarily caused by direct mechanistic effects.